"How do I send an Email?": Technology Challenges for First-Year Students in the College Library. Issue 3 (21st September 2015) - Eichelberger, Michelle; Imler, Bonnie Brubaker
Abstract : Purpose: – The purpose of this paper is to identify the ability of college freshmen to successfully use common academic software and manage files. Design/methodology/approach: – In total, 39 college freshmen from three college campuses were recruited for the study. An online test environment and screen recording software were used to measure student proficiency in using PDFs, Microsoft Word, Microsoft PowerPoint, Microsoft Excel, Gmail, and Windows. Data were collected in September 2013. Findings: – Student use of academic technology is common, but their software skills are not comprehensive or deep. Students were most proficient at using PDFs and Microsoft Word. Microsoft Excel tasks were the most difficult for the students, and many struggled to use Gmail to compose a message and send an attachment. Students were able to open a PowerPoint document and view a slideshow, but they were less comfortable navigating the software's printing environment. Originality/value: – Having concrete data about student technology skills, rather than anecdotal data from reference desk interactions, can help librarians design improved instruction and tutorials that target areas of student technology weakness.